Acceleration of cutaneous wound healing by brassinosteroids. Issue 5 (12th August 2013) - Esposito, Debora; Rathinasabapathy, Thirumurugan; Schmidt, Barbara; Shakarjian, Michael P.; Komarnytsky, Slavko; Raskin, Ilya
Abstract Brassinosteroids are plant growth hormones involved in cell growth, division, and differentiation. Their effects in animals are largely unknown, although recent studies showed that the anabolic properties of brassinosteroids are possibly mediated through the phosphoinositide 3‐kinase/protein kinase B signaling pathway. Here, we examined biological activity of homobrassinolide (HB) and its synthetic analogues in in vitro proliferation and migration assays in murine fibroblast and primary keratinocyte cell culture. HB stimulated fibroblast proliferation and migration and weakly induced keratinocyte proliferation in vitro. The effects of topical HB administration on progression of wound closure were further tested in the mouse model of cutaneous wound healing. C57BL/6J mice were given a full‐thickness dermal wound, and the rate of wound closure was assessed daily for 10 days, with adenosine receptor agonist CGS‐21680 as a positive control. Topical application of brassinosteroid significantly reduced wound size and accelerated wound healing in treated animals. mRNA levels of transforming growth factor beta and intercellular adhesion molecule 1 were significantly lower, while tumor necrosis factor alpha was nearly suppressed in the wounds from treated mice. Our data suggest that topical application of brassinosteroids accelerates wound healing by positively modulating inflammatory and reepithelialization phases of the wound repair process, in part by enhancing Akt signaling in the skin at the edges of the wound and enhancing migration of fibroblasts in the wounded area. Targeting this signaling pathway with brassinosteroids may represent a promising approach to the therapy of delayed wound healing.